ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REVISIT INTENTION PADA WISATAWAN AIR TERJUN SIMBILULU KABUPATEN PAK PAK BHARAT - Tumangger, Mhd. Arifta Pulung; Syahriza, Rahmi; Daulay, Aqwa Naser (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025, 2025)
This study aims to determine the effect of facilities, accessibility, security, and services related to revisit intention on simbilulu waterfall tourists in Pak Pak Bharat Regency. The method applied in this research is multiple linear regression analysis. The population in this study were the number of tourists who visited Simbilulu waterfall in 2024 with a total of 587 people. The sample collection technique is non probability sampling using the slovin formula obtained a sample of 86 people. The results of the study are: Facilities play a positive role related to the revisit intention of Simbilulu Waterfall tourists. Accessibility affects the revisit intention of Simbilulu Waterfall tourists. Security affects the revisit intention of Simbilulu Waterfall tourists. Service has a significant positive effect on the revisit intention of Simbilulu Waterfall tourists and is the most dominant variable. Facilities, accessibility, security, and services carried out simultaneously or simultaneously have an impact on the revisit intention of Simbilulu Waterfall tourists. When these variables are analyzed together, they show a meaningful contribution to tourists' decision to return to visit the destination. The manager's efforts to increase tourists' revisit intention at Simbilulu Waterfall, the manager should continue to improve facilities, improve accessibility, and maintain security.